How to improve governance a new framework for analysis and action - De Ferranti, David M. (Brookings Institution Press, 2009)
"Emphasizes the need for a comprehensive analytical framework that considers transparency, accountability, governance, and corruption throughout the calculus. Discusses how it can be applied to different countries to help analyze the current situation and identify potential areas for improvement, assessing their relative feasibility and the steps needed to promote them"--Provided by publisher.